2014
DOI: 10.1016/j.nucengdes.2014.03.042
|View full text |Cite
|
Sign up to set email alerts
|

Weld residual stresses near the bimetallic interface in clad RPV steel: A comparison between deep-hole drilling and neutron diffraction data

Abstract: The inner surface of ferritic steel reactor pressure vessels (RPV) is clad with strip welded austenitic stainless steel primarily to increase the long-term corrosion resistance of the ferritic vessel. The strip welding process used in the cladding operation induces significant residual stresses in the clad layer and in the RPV steel substrate, arising both from the thermal cycle and from the very different thermal and mechanical properties of the austenitic clad layer and the ferritic RPV steel This work measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…Residual stress measurements presented in this paper were carried out on 42 mm (post-weld heat-treated) and 58 mm (as-welded) thick plates, whereas RPVs have much thicker walls, typically around 180 -200 mm. Measurements in previous work by James et al [9] showed that the residual stress in a clad plate was significantly affected by reducing the thickness of the plate from 80 mm to 30 mm. Rybicki et al [36] extracted 32 mm thick samples from a larger clad plate, and found that reducing the thickness of the cladding by half from 8.9 to 4.4 mm significantly increased the magnitude of residual stress in the cladding.…”
Section: The Effect Of Thickness On Cladding Residual Stressmentioning
confidence: 95%
See 1 more Smart Citation
“…Residual stress measurements presented in this paper were carried out on 42 mm (post-weld heat-treated) and 58 mm (as-welded) thick plates, whereas RPVs have much thicker walls, typically around 180 -200 mm. Measurements in previous work by James et al [9] showed that the residual stress in a clad plate was significantly affected by reducing the thickness of the plate from 80 mm to 30 mm. Rybicki et al [36] extracted 32 mm thick samples from a larger clad plate, and found that reducing the thickness of the cladding by half from 8.9 to 4.4 mm significantly increased the magnitude of residual stress in the cladding.…”
Section: The Effect Of Thickness On Cladding Residual Stressmentioning
confidence: 95%
“…However, the residual stress is not completely erased [2][3][4] because additional stresses are generated upon cooling due to the difference in thermal expansion coefficient between the cladding and parent materials. The residual stress in pressure vessel steel clad with stainless steel has been well characterised in previous work using modelling techniques [2,4] and experimental measurements [2][3][4][5][6][7][8][9][10]. In general, material which has been post-weld heat-treated contains high tensile residual stress in the cladding of around 200 -400 MPa, and lower-magnitude tensile or compressive stress in the parent [3,7,11].…”
Section: Introductionmentioning
confidence: 99%
“…Many attempts have been done to figure out the relationship between different cutting parameters/conditions and the induced RSes using experimental [6][7][8], analytical modeling [9][10][11], finite element modeling [12][13][14], and various combinations of them [15][16][17] in various machining operations [18][19][20]. The experimental investigations were carried out via measuring the RSes using different measuring methods such as ring core method [21], hole drilling technique [22], deep-hole drilling [23], slope cutting method [24], contour method [25], synchrotron diffraction [26] method, XRD method [27], and neutron diffraction method [28]. Among all these measuring techniques, XRD and hole drilling technique are the most commonly used in machining applications.…”
Section: Introductionmentioning
confidence: 99%